A comparative study between conventional methods and Vidas UP Salmonella (SPT) to investigate salmonella species from local and imported meat (Baghdad Science Journal, 2015)
The study was preformed for investigating of Salmonella from meat, and compared Vidas UP Salmonella (SPT) with the traditional methods of isolation for Salmonella , were examined 42 meat samples (Beef and Chicken) from the Local and Imported From local markets in the city of Baghdad from period December 2013 -February 2014 the samples were cultured on enrichment and differential media and examined samples Vidas, and confirmed of isolates by cultivation chromgenic agar, biochemical tests ,Api20 E systeme , In addition serological tests , and the serotypes determinate in the Central Public Health Laboratory / National Institute of Salmonella The results showed the contamination in imported meat was more than in the local meat 11.9% and 2.3 %, respectively, also recorded the highest isolation of Salmonella from chicken meat compared with beef meat 9.5% and 4.7%, respectively, where isolated 3 serotype (7.14%) from imported chicken meat include S.typhimurium S.entertidis and S.livingstone at16.6% for each of them and 1 serotype (2.3%) isolate from local chicken meat include S.hadar 16.6%. The study recorded for the first time isolate of S. living stone in Iraq from imported chicken. While isolated 2 serotype (4.7%) isolate from imported beef included S. dublin and S. antum at 16.6% each of them .the sensitivity of antibiotics , was studies the results showed that it was resistant to each of Trimethprime Cetazidime Ampicillin Chloromphenicol, Ceftriaxone, and Amoxicillin (100, 66.6 ,33.3, 16.6 , 16.6 , and 16.6 ) % respectively , but sensitivite to Imipenem and Ciprofloxacin at 100% and confirmed the results that the Vidas technique better than traditional methods for speed and accuracy of their results.